Recurrent suicide attempts affect normalization of HPA axis dysregulation after recovery from major depression - Hennings, Johannes M.; Ising, Marcus; Uhr, Manfred; Holsboer, Florian; Lucae, Susanne (Frontiers in Psychiatry, 2022)
More than 700 000 people worldwide die by suicide every year, and the number of suicide attempts is estimated as 20-times higher, most of them being associated with psychiatric disorders, especially major depression. The knowledge about effective methods for preventing suicide attempts in individuals at high risk for suicide is still scarce. Dysregulation of the neuroendocrine stress response system, i.e., the hypothalamic-pituitary-adrenocortical (HPA) axis, is one of the most consistent neurobiological findings in both, major depression and suicidality. While HPA axis is mostly overactive in depression, individuals with a history of suicide attempts exhibit an attenuated hormonal response to stress. It is unknown, however, whether the HPA axis is constantly attenuated in repeated suicide attempters or whether it regains normal responsivity after recovery from depression. Using the combined dexamethasone suppression/corticotropin releasing hormone (dex/CRH) test, we assessed HPA axis regulation in acute depression (N=237) and after recovery with respect to previous suicide attempts. Patients without previous suicide attempts show a normalization of the stress hormone response to the second dex/CRH (basal ACTH response, cortisol response) after recovery from acute depression, while patients with multiple previous SA show an increased ACTH response. The change of HPA axis responsivity in patients with only one previous SA lies between the response pattern of the other groups with no change in HPA axis reactivity. Our findings suggest that patients with a history of suicide attempts belong to a subgroup of individuals that exhibit a distinct pattern of stress hormone response during acute depression and after recovery. Future studies may extend our approach by investigating additional psychological stress tasks to gain a broader understanding of the stress pathology of recurrent suicide attempters.